Transport in a stochastic double diffusivity model - Chattopadhyay, Amit K.; Parisis, Konstantinos; Konstantinidis, Avraam; Aifantis, Elias C. (Meccanica, 2023)
A recent study analyzed the role of stochastic perturbations on the interface dynamics of two interacting species within a double-diffusivity framework, involving double diffusion models. The model relied on a restricted translation–reflection (TR) symmetry manifold, leading to a single variable description. The present study generalizes this model for a TR symmetry violating system that does not permit reduction to a single variable dynamics, leading to a hitherto unseen stochastic resonance (SR), a mechanism that indicates discrete, rather than a continuous, mode of energy transport. The SR exhibited by the model captures the signature fast transport observed in stochastically driven dynamics of nanopolycrystals, that previous deterministic models failed to emulate. We show that the speed of transfer relates to the strength of energy cross-correlations between the two diffusing species communicating through interface dynamics that eventually drives the energy throughput and identifies the role of stochasticity in nanopolycrystalline transport.
CRIS-Team Scopus Importer:2023-08-11
Keywords: Double diffusion; Interface dynamics; Nanopolycrystal; Stochastic